Structural integrity of reinforced concrete slabs of some selected existing buildings based on field assessment - Akingbonmire Samuel Lambe; Afolayan Joseph Olaseinde (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
Quality assurance and reinforcement detailing may affect the primary function of a reinforced concrete slab to transfer the load upon it by bending. This paper is focused on a probability-based approach to investigate the structural integrity of the reinforced concrete slabs of two selected buildings at a university campus. The in situ strength of all accessible floor slabs was measured using the Schmidt rebound hammer and Ultrasonic pulse velocity tester. The loadings on the slabs were analysed using Orion Software on the structural layouts of the two buildings. The integrity of the slabs, measured by their reliability indices, considering the yielding of the steel and deflection criteria, were estimated using the first-order reliability procedure. The computed indices were related to a target reliability index of 3.8 for the ultimate limit state and 1.5 for the serviceability limit state, chosen for a 50-years reference period of Class RC2 structural members according to BS EN 1990:2002+A1:2005. Generally, the safety indices decrease as the applied loads/moments increase for all the slabs in the two buildings. Although the estimated safety indices reveal that the slabs are over-designed, some of the slab panels in one of the buildings will fail the deflection criterion when loaded to about 80% of their ultimate capacity. Based on this assessment, a disparity in quality assurance between the two buildings has been established.